Insulin-like growth factor-1 as predictive factor of difficult laryngoscopy in patients with GH-producing pituitary adenoma: A pilot study. (December 2021) - Iacovazzo, Carmine; de Bonis, Clemmaria; Sara, Rosario; Marra, Annachiara; Buonanno, Pasquale; Vargas, Maria; Cavallo, Luigi Maria; Servillo, Giuseppe
Highlights: The upper airway modifications in patients with GH-secreting adenoma makes the anaesthesiological management more complicated. The predictive scores of difficult intubations do not appear to be able to predict a difficult airway of these patients. Preoperatory serum values of IGF-1 appears to predict difficult laryngoscopy. Preoperative serum IGF-1 levels can be integrated into new predictive scores of difficult airways. Abstract: Background: Growth hormone (GH)-producing pituitary tumors account for 10 to 15% of pituitary tumors. The hypersecretion of GH may induce changes in the airway anatomy through the activation of Insulin-like Growth factor 1(IGF-1) pathway. We sought investigate the role IGF-1 as a potential predictive factor of difficult laryngoscopy in patients with GH-producing pituitary adenoma. Methods: This study was a single center retrospective study. We included 33 patients undergoing transsphenoidal resection of GH-producing pituitary. We recorded demographic data, el-Ganzouri risk index (EGRI) and modified Look-Evaluate-Mallampati-Obstruction-Neck mobility (mLEMON) score, and pituitary hormone plasma levels. We performed ordinal logistic regression to analyze the relationship between IGF-1 and EGRI, mLEMON, and Cormack-Lehane Grade score and a multiple logistic regression to test the capability of EGRI, mLEMON and IGF-1 levels to predict Cormack-Lehane score. Receiver operating curve (ROC), area under the curve (AUC), and cut-off value of IGF-1 were calculated. Results: Only 14 (42.8%) and 12 (36.36%) patients showed predictive factors of difficult intubation according to EGRI and mLEMON score, respectively. IGF-1 significantly correlated with Cormack-Lehane ( p = 0.005879) but not with mLEMON and EGRI ( p = 0.3080 and 0.4146, respectively). In multiple regression model IGF-1 correlated only with Cormack-Lehane grade ( p = 0.0089). Area under ROC was 0.8571 and cut-off value of IGF-1 was 186.15 ng/ml. Conclusion: Higher IGF-1 levels correlate with the probability of having a higher Cormack-Lehane score; classical bedside scores, such as mLEMON and EGRI, were not able to predict difficult laryngoscopy in our population.